Effects of alkalinity-controlling chemicals on biofilter performance and sludge properties in freshwater recirculating aquaculture systems - Qi, Wanhe; Vielma, Jouni (Elsevier, 2026)
This study aims to enrich potassium (K) content in sludge from recirculating aquaculture systems (RAS) by replacing sodium (Na)-based alkalinity-controlling chemicals with K-based derivates. Nine identical pilot-scale RAS rearing rainbow trout (Oncorhynchus mykiss) were operated for 10 weeks in triplicate treatments with K2CO3, NaHCO3, and NaOH as alkalinity-controlling chemicals. Water and sludge samples were collected weekly from the RAS for water quality and sludge property measurements. Results showed that K2CO3 significantly increased K concentrations, reaching average values of 190 mg/L in water samples and 180 mg/kg in sludge samples. These levels were 17–20 times and 14 times higher than those observed in NaHCO3 and NaOH treatments, respectively. All treatments achieved satisfactory biofilter performance (TAN < 1 mg/L and NO2--N < 0.2 mg/L), and good fish production performance (FCR=0.96–1.17, survival > 95%). Significant accumulation of Na in rearing water from NaHCO3 and NaOH treatments was observed with 133 ± 7 mg/L and 136 ± 2 mg/L at the end of experiment, respectively, which are far above phytotoxic Na threshold of 50 mg/L. In contrast, K2CO3 treatment maintained low and stable Na levels over sampling period, ranging from 4.0 ± 1.3 mg/L to 6.3 ± 0.6 mg/L. No difference observed among treatments on other sludge (TN, TP, DM, TSS and SVI30) and water (TN, TP, Ca, Mg, S, and Si) parameters. This study confirms that K2CO3 as an alkalinity-controlling chemical in RAS is a feasible and synergistic solution in unifying alkalinity adjustment and producing a K-rich fertilizer from RAS sludge, which enhances the sustainability and circularity of aquaculture production.
Keywords: sludge valorization; fertilizer; buffering agents; potassium supplement; nitrification; circular economy